Comportamento em fadiga de hastes femorais para artroplastia de quadril com superfícies modificadas - Oliveira, Bruno José Silva de (2015)
Nowadays, titanium and its alloys are the materials of choice for the production of implants for hip arthroplasty, a surgery that aims for the improvement of the quality of life of patients that bear articular pathologies of the hip. With the increase of life expectancy, it becomes more and more important that these implants withstand greater times of implantation, avoiding revision surgeries, which represent higher costs and risks. Today, this need is approached by different ways, among them the functionalization of surfaces, that permit better osseointegration of the prosthesis at the site of implantation and, consequently, better results on the application of products in the long term. One of the ways to perform this functionalization is through chemical etching, one of which (H3PO4+NaOH) has been chosen to perform modification of surfaces previously treated by titanium plasma spray (TPS+AQ) on finished femoral prostheses. As a control, another group of prostheses was employed, treated with technology already in the market, coated by titanium plasma spray with posterior deposition of two phases of calcium phosphate with different solubility (TPS+HA). The prostheses were submitted to topographical analyses via SEM, analyses of roughness profiles and increase of effective surface area by confocal microscopy and transversal analyses of coatings via SEM, subsequently treated by image analysis software for determination of attributes of porous coatings according to ASTM F1854. After that, all prostheses were tested to evaluate their fatigue behavior according to ISO 7206-4 and the presence of cracks via penetrant liquid testing. All the specimens survived the fatigue test, refuting the hypothesis that the modification via TPS+AQ reduces the fatigue resistance of femoral stems when compared to a control group, TPS+HA, under a normalized test protocol.